A comparison of recommendations and received treatment for mood and anxiety disorders in a representative national sample - Benjamin A. R. Woolf; Jeanne V. A. Williams; Dina H. Lavorato; Andrew G. M. Bulloch; Scott B. Patten (BMC Psychiatry, 2017)
Abstract Background The exact nature of treatment and management recommendations made, and received, for mood and anxiety disorders in a community population is unclear. In addition, there is limited evidence on the impact of recommendations on actual receipt of treatment or implementation of management strategies. We aim to describe the frequency with which specific recommendations were made and implemented; and thus assess the size of any gap between the recommendation and implementation of treatments and management strategies. Methods We used the Survey ‘Living with a Chronic Condition in Canada - Mood and Anxiety Disorders (SLCDC-MA), a unique crossectional survey of a large (N = 3358) and representative sample of Canadians with a diagnosed mood or anxiety disorder, which was conducted by Statistics Canada. The survey collected information on recommendations for medication, counselling, exercise, reduction of alcohol consumption, smoking cessation and reduction of street drug use. We also estimate the frequency that recommendations are made and followed, as well the impact of the prior on the latter. We consulted people with lived experience of the disorders to help interpret our results. Results The results generally showed that most people would receive recommendations, almost all for antidepressant medications (94.6%), with lower proportions for the other treatment and management strategies (e.g. 62.1 and 66% for counselling and exercise). Most recommendations were implemented and had an impact on behaviour. The exception to this was smoking reduction/cessation, which was often not recommended or followed through. Other than with medication, at least 20% of the population, for each recommendation, would not have their recommendation implemented. A substantive group also exists who access treatments, and employ various management strategies, without a recommendation. Conclusions The results indicate that there is a gap between recommendations made and the implementation of treatments. However, its size varies substantially across treatments.